Proven solutions for improving supply chain performance - Pegels, C. Carl (Proven solutions series., 2005)
Proven Solutions for Improving Supply Chain Performance is a collection of about 175 descriptions of scientific management studies in the management of supply chains. Each one of the descriptions of the scientific studies is presented in readable and understandable form for individuals who probably have not had the statistical and scientific education and training to fully understand the underlying studies.The book is significantly different from the popular management literature, which is generally based on "armchair" theories that have little basis on fact, and seldom have been scientifically verified. Although the book is targeted for the supply chain manager/administrator, it can also be used as a supplementary reader in such courses as Operations Management, Service Systems Management, Manufacturing Management, Purchasing Management, and, of course, in Supply Chain Management courses.